Lactate and lactylation in breast cancer: current understanding and therapeutic opportunities - Lan Huang; Xuemei Chen; Meina Yan; Ze Xiang; Jian Wu (Cancer Biology & Medicine, 2025)
Breast cancer (BC) has the highest prevalence among cancers specific to women, and its incidence rates are increasing in many countries. Subtypes of BC, including HER2-positive or triple-negative BC, exhibit differing treatment responses; consequently, demand for personalized therapy is increasing, and relevant precision medicine strategies are under development. Aerobic glycolysis in cancer cells can lead to excessive lactate production, which in turn promotes lactylation and influences tumor cell behavior. Epigenetic alterations and metabolic reprogramming are prominent characteristics of tumors. Because lactate and lactylation are important in cancer, further investigation of the mechanisms underlying lactate metabolism and lactylation, and the development of therapeutic strategies targeting these processes, are topics of increasing interest. This review describes current research on lactate metabolism and lactylation in BC, thus offering new perspectives for advancing treatment and management toward more precise and personalized approaches that will ultimately increase BC survival rates and patient quality of life.